Perempuan Arabia dalam Lingkaran Perkawinan di Era Pra-Islam - Wardah Nuroniyah (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2019)
The issue of the position of women is a matter that invites much debate among feminists and observers of gender equality. Different perspectives and paradigms of thinking lead to differences of opinion in resolving these problems. This paper examines the position of women in the Islamic marriage system by reflecting it on the marriage system in the pre-Islamic era through a historical approach to understanding the position of women in the marriage environment. History shows that the position of women in marriage in pre-Islamic times has an unfavorable position. This is due to the division of roles according to their respective gender, where in the end it creates inequality in social life. In Arabian society, men are tasked with defending and maintaining all family members, responsible for meeting all the needs of family members. Consequently men monopolize leadership at all levels. Patriarchal culture dominates, so marriage becomes more synonymous with a contract of sale where women are considered to be nothing more than an object being sold. In addition, the killing of female infants is a custom in Arab society and women who are caught in war are usually made into concubines. Islam came by renewing the Arab community’s marriage system. Various innovations introduced by the Koran to improve the dignity of women at that time were only the initial stages, which were in accordance with the patrilineal context. Therefore, patrilineal at that time was a situation which had to be consolidated by Islam, and not institutionalized. An understanding of the pre-Islamic marriage system is important in order to be able to see clearly how the position of women in the Islamic marriage system is actually far more advanced than before.